PENGARUH KUALITAS LAYANAN TERHADAP WORD OF MOUTH (WOM) DENGAN KEPUASAN KONSUMEN SEBAGAI MEDIASI (Studi pada Perusahaan Organda (PO) Slamet di Pati) - Utomo, 09.05.51.0041 (Students Journal of Economic and Management, 2014)
Quality of service is one of the key factors for the success of a company as an industry that offers services products. Quality of service can affect customer satisfaction. Customer satisfaction is a significant determinant of repeat purchases, information from positive word of mouth and customer loyalty. Satisfied customer will take action word of mouth (WOM). Word of mouth (WOM) marketing is a business that triggers consumers to discuss, promote, recommend and sell products / brands to other customers. Population in this research is that consumers Organda Company (PO) Slamet, J1. Starch Kingdom - Tayu, KM 3, in Pati. And the sample in this study was 100. The analysis technique used is the Path Analysis. The results showed that: (1). service quality and significant positive effect on customer satisfaction. (2). customer satisfaction and a significant positive effect on word of mouth. (3). affect the quality of service by word of mouth consumer satisfaction as an intervening variable. Keywords : Quality Service, Consumen Satisfaction, Word Of Mouth